A literature review and meta-analysis on the effects of ADHD medications on functional outcomes. (April 2020) - Boland, Heidi; DiSalvo, Maura; Fried, Ronna; Woodworth, K. Yvonne; Wilens, Timothy; Faraone, Stephen V.; Biederman, Joseph
Abstract: Objective: To conduct a systematic review and meta-analysis of literature from large databases and registries to assess the effects of ADHD medication on associated functional outcomes. Study design: A literature search was performed in PubMed, PsycINFO, MEDLINE, and Web of Science for articles published prior to January 2019. Sample size, age range, country of origin, medication type, number of functional events and non-events, odds ratios and hazard ratios, and means and standard deviations were extracted. Random-effects meta-analyses were conducted for 21 studies examining functional outcomes. Results: 40 articles were included. The majority suggest a robust protective effect of ADHD medication treatment on mood disorders, suicidality, criminality, substance use disorders, accidents and injuries, traumatic brain injuries, motor vehicle crashes, and educational outcomes. Similarly, the meta-analyses demonstrated a protective effect of medication treatment on academic outcomes, accidents and injuries, and mood disorders. Conclusions: These findings suggest that ADHD medication treatments are associated with decreases in the risks for a wide range of ADHD-associated functional outcomes supporting efforts aimed at early diagnosis and treatment of individuals with ADHD. Highlights: ADHD medication use is associated with decreased risk of outcomes including motor vehicle crashes and depression. Early diagnosis and treatment of ADHD may help alleviate the risk of these harmful outcomes. There were variable but largely positive findings associated with lowered rates of mood disorders, substance use disorders, criminality, suicidality, traumatic brain injuries, motor vehicle crashes, injuries, and academic outcomes and ADHD medication use